Étude socio-terminologique du vocabulaire médical cilubÃ - Musampa, Emmanuel Kambaja (Lexikos, 2007)
Abstract: Socioterminological Study of the Ciluba Medical Vocabulary. At the conclusion of an investigation (led by Mbujimayi, in the Democratic Republic of the Congo) among medical and paramedical staff who are speakers and users of Ciluba, a Bantu language classified by Guthrie in linguistic zone L31, we have collected, by means of recourse to the docu-mentary evidence, 150 French medical terms translated into Ciluba. These terms have been sub-mitted to a twofold socioterminological analysis: a morphosyntactical and a semantic analysis. It deals with analyzing a medical terminology, still basically conveyed in French. This analysis leads to a morphosyntactic and semantic structure which shows that the medical vocabulary in Ciluba has become general, containing more commonplace terms from classes 7 and 12 than from the other classes. These terms are polysemic, metaphoric, metonymic, synonymic or characterized by synecdoche and semantic shift. Contrary to the established tradition in terminology, monosemy is not the rule. This study deals with African terminology, in this way preparing for a bilingual medi-cal dictionary French–Ciluba. Keywords: TERMINOLOGY, GENERAL VOCABULARY, MORPHOSYNTACTIC STRUC-TURE, SEMANTIC STRUCTURE, METAPHOR, POLYSEMY, SYNONYMY, METONOMY, MONOSEMY Résumé: À l’issue d’une enquête (menée à Mbujimayi, en République Démocratique du Con-go) auprès du personnel médical et paramédical locuteur et utilisateur du cilubà, langue bantoue, classifiée par Guthrie dans la zone linguistique L31, nous avons récolté, grâce au recours préalable au dépouillement documentaire, 150 termes médicaux français traduits en cilubà. Ces termes ont été soumis à une analyse socio-terminologique double: une analyse morphosyntaxique et une ana-lyse sémantique. Il s’agit d’analyser une terminologie médicale, encore essentiellement véhiculée en français. Cette analyse aboutit à une structure morphosyntaxique et sémantique révèlant que le vocabulaire médical en cilubà est «banalisé», il contient plus de termes simples de la classe 7 et ceux de la classe 12 que les autres. Ces termes sont polysémiques, métaphoriques, métonymiques, synonymiques, ou marqués par la synecdoque et le glissement sémantique. La monosémie n’est pas la règle, contrairement à la vieille tradition en terminologie. Cette étude s’insère dans la terminolo-gie africaine et prépare ainsi à un dictionnaire médical bilingue français–cilubà. Mots clés: TERMINOLOGIE, VOCABULAIRE BANALISÉ, STRUCTURE MORPHOSYN-TAXIQUE, STRUCTURE SÉMANTIQUE, MÉTAPHORE, POLYSÉMIE, SYNONYMIE, MÉTONY-MIE, MONOSÉMIE